Clinical research Buerger’s disease as an indicator of socioeconomic development in different societies, a cross-sectional descriptive study in the North-East of Iran - Fazeli, Bahare (Archives of Medical Science, 2010)
Introduction: Nowadays, Buerger’s disease (BD) is more common in the developing countries of Asia. Although its prevalence is going to decrease in the developed countries, its decline rate is not in parallel with that for smoking in these countries. Since the number of BD patients reported to MVasRc is increasing annually and its pathogenesis is unknown, the aim of the study was to investigate the smoking habits and socioeconomic status of the patients corresponding with Shionoya’s criteria. Material and methods: Poverty line was the key factor of economic condition. Hygiene, education, professional occupation, long-term unemployment and healthy work were considered as social indices. Patients under the poverty line in addition to weakness in more than two social indices were included in low socioeconomic classification. Results: From the total of 86 patients who reported to MVasRc during the 22-month study period, 71.6% and > 95% were new cases of BD and in low socioeconomic status respectively. Smoking ranged from 2 to 80 cigarettes/day. The duration of smoking before the onset of BD varied from 2 months to 35 years. Conclusions: There is a lack of correspondence between BD and decline in the prevalence of smoking in developed countries. Also, duration and smoking habit varied in the studied patients. On the other hand, the strong dependence of BD on low socioeconomic conditions, as revealed in this research, implies that socioeconomic status may be a risk factor for initiation of BD. Moreover, the prevalence of BD might be an indicator of socioeconomic development in different societies.